Strategies for Utilizing Productive Zakat in Mustahik Economic Empowerment in Indonesia: A Systematic Literature Review - Achmad Junaidi; Bustomi Arisandi (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the strategy of utilizing productive zakat as an instrument of economic empowerment and poverty alleviation in Indonesia. Through the Systematic Literature Review (SLR) method, this study examined 28 selected scientific articles from the range of 2015 to 2026 sourced from the Google Scholar database and reputable journals. The data selection process uses the PRISMA protocol to ensure the validity and transparency of the findings. The results of the study show that the effectiveness of productive zakat is highly dependent on three main pillars: the accuracy of mustahik selection, the intensity of business assistance, and the use of digital technology in program monitoring. This study found that the transformation of mustahik status into muzakki cannot be achieved only through the provision of capital, but requires the integration of financial literacy and spiritual guidance. In addition, distribution digitalization was found to be a key factor in increasing program transparency and reach in the post-pandemic era. The implications of this study emphasize the need to standardize the productive zakat management model for Amil Zakat Institutions (LAZ) in order to optimize the economic sustainability of the ummah in the long term.